Evoked responses to transcranial and electrical stimulation during isometric and lengthening contractions of the soleus muscle - Alexandrou, Anna Maria (2011)
The aim of this study was to assess differences in motor control between isometric and lengthening contractions of the soleus muscle. Evoked responses to TMS (MEPs) and electrical stimulation of the peripheral nerve (H-reflexes) where recorded at rest and during isometric and lengthening contractions of the soleus muscle at 20%, 40%, 60% and 80% MVC. Torque and background EMG were averaged over a time window of 100ms prior to stimulation. MEPs were found to be significantly lower (P < 0.05) during lengthening contractions compared to isometric contractions at 40%, 60% and 80% MVC (10.95 ± 0.05 mV vs 9.93 ±0.06 mV ; 1.47 ± 0.07 mV vs 9.7 ± 0.08 mV; 11.48 ± 0.08 mV ± vs 10.14 ± 0.07 mV). The H-reflex-to-Mmax ratio was significantly lower (P < 0.05) during passive lengthening compared to the passive isometric condition (2.5 ± 1.11 mV vs 1.4 ±0.88 mV). In an active muscle, the H-reflex-to-Mmax ratio was similar between isometric and lengthening modes of contraction. Torque production during passive lengthening (1.8 ± 2.8 Nm vs 4.6 ± 3.2 Nm) and at 20% MVC lengthening (215.25 ± 68.3 Nm vs 300.8 ± 155 Nm) was higher (P < 0.05) compared to the corresponding torque produced in isometric conditions. MEPs represent the excitability of both supraspinal and spinal neurons; H-reflex, on the other hand, reflects only the excitability of the spinal MN pool. Therefore, it was concluded that the motor cortex generates a descending command of lower amplitude in the case of lengthening contractions. This, however, could not be considered as neural inhibition, since recorded torque during muscle lengthening was similar or higher compared to the torque recorded during isometric muscle actions.